Haritaki: Treasure of Ayurveda - Garg, Nisha; Panda, Srikanta Kumar (International Research Journal of Ayurveda & Yoga, 2022)
Background-Traditional herb named Haritaki (Terminalia Chebula) commonly known as Harada is a very potential and useful drug that is having a very divine place in ayurveda. Its explanation in various nighantus texts in very beginning shows its immense importance. Its various properties, varieties and its different useful phytoconstituents makes it multipurpose and valuable drug. It is having anti aging, anti oxidant, anti fungal, anti bacterial, anti arthritic and also having potential for preventing skin aging. Review methods: The studies done in previous years were found using Medline, Embase, Google scholar, pub med and by manual search. Studies conducted for determining the role of different phyto-constituents of haritaki specifically were included in this study. Results-It has been tried to keenly understand the role of different phyto constituents in particular and exploring some new concepts related to it in this review. Phytochemicals of Terminalia chebula are dealt in detail with its potential effects on various systems of human body and its potentiality as a therapy tool. Conclusion: After reviewing several articles and ancient texts it has been concluded that Haritaki is an immense drug available in our ayurveda which is literally not less than a treasure.